THE EFFECT OF THIRD PARTY FUNDS OF WADI`AH AND SAVING WIROAH GIRO ON PROFIT PT. SHARIA BRI BANK - Muzakir Muzakir; Yulius Dharma (Journal of Malikussaleh Public Economics, 2018)
This study aims to determine the effect of Third Party Funds Giro Wadi'ah and Wadi'ah Savings on PT. BRI Syariah Bank from 2008 to 2017. This study uses secondary data by processing data on a quarterly basis within a period of 10 years. From the results of the research partially, the Giro Wadi'ah variable has a partially significant influence on the dependent variable of net income and the Wadi'ah Savings variable has a partially significant influence on the dependent variable of net income. While the simultaneous test of Giro Wadi'ah and Tabungan Wadi'ah variables simultaneously or together has a significant effect on the dependent variable of net income at PT. BRI Syariah Bank.